2020
DOI: 10.14444/7146
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Minimally Invasive Lumbar Fusion Using Multimodal Analgesic Management in the Ambulatory Surgery Setting

Abstract: Background: The transition of minimally invasive (MIS) spine surgery from the inpatient to outpatient setting has been aided by advances in multimodal analgesic (MMA) protocols. This clinical case series of patients demonstrates the feasibility of ambulatory MIS transforaminal lumbar interbody fusion (TLIF) and lateral lumbar interbody fusion (LLIF) procedures while using an enhanced MMA protocol.Methods: Consecutive MIS TLIF or LLIF procedures with percutaneous pedicle screw fixation and direct decompression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 63 publications
1
23
0
6
Order By: Relevance
“…[28][29][30] In the study by Parrish et al, a novel MMA protocol was established and validated for both TLIF and LLIF patients in an outpatient setting. 18 Given notable differences in postoperative narcotic consumptions and PONV between cohorts, our study may suggest the need for procedure specific MMA protocols in MIS fusion.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…[28][29][30] In the study by Parrish et al, a novel MMA protocol was established and validated for both TLIF and LLIF patients in an outpatient setting. 18 Given notable differences in postoperative narcotic consumptions and PONV between cohorts, our study may suggest the need for procedure specific MMA protocols in MIS fusion.…”
Section: Discussionmentioning
confidence: 81%
“…Although our study reported no significant differences in postoperative recovery through RRs, previous literature has identified patients undergoing LLIF to have a faster initial recovery. 3,18 Moreover, no difference in t1-year rates of arthrodesis and postoperative complications with exception of PONV were noted. The lack of significant differences in longterm clinical outcomes between TLIF and LLIF agreed with existing studies.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…As such, use of tramadol, which is a known weak l-opioid receptor agonist, was implemented to minimize the use of more potent opioids (oxycodone). While our protocol does incorporate the use of some narcotic medications, their use, as described in the study of discussion, 23 is at half dosage, as recommended by the FDA, 5 and is primarily for breakthrough pain in the postoperative recovery room as well as for patients discharged on postoperative day 0. Furthermore, there is sufficient evidence that controlling acute pain after surgery can reduce chronic pain.…”
mentioning
confidence: 99%
“…We read with great interest the work by Dr Parrish and colleagues describing their package of multimodal analgesia (MMA) for lumbar surgery in the ambulatory setting. 1 We applaud their efforts to highlight the importance of adequate analgesia on rapid recovery after spine surgery.…”
mentioning
confidence: 99%